Microglial MHC class II is dispensable for experimental autoimmune encephalomyelitis and cuprizone‐induced demyelination. Issue 8 (7th June 2018) - Wolf, Yochai; Shemer, Anat; Levy‐Efrati, Liron; Gross, Mor; Kim, Jung‐Seok; Engel, Adrien; David, Eyal; Chappell‐Maor, Louise; Grozovski, Jonathan; Rotkopf, Ron; Biton, Inbal; Eilam‐Altstadter, Raya; et al.
Abstract: Microglia are resident immune cells in the CNS, strategically positioned to clear dead cells and debris, and orchestrate CNS inflammation and immune defense. In steady state, these macrophages lack MHC class II (MHCII) expression, but microglia activation can be associated with MHCII induction. Whether microglial MHCII serves antigen presentation for critical local T‐cell restimulation in CNS auto‐immune disorders or modulates microglial signaling output remains under debate. To probe for such scenarios, we generated mice harboring an MHCII deficiency in microglia, but not peripheral myeloid cells. Using the CX3 CR1 CreER ‐based approach we report that microglial antigen presentation is obsolete for the establishment of EAE, with disease onset, progression, and severity unaltered in mutant mice. Antigen presentation‐independent roles of microglial MHCII were explored using a demyelination model induced by the copper chelator cuprizone. Absence of microglial I‐A b did not affect the extent of these chemically induced white matter alterations, nor did it affect microglial proliferation or gene expression associated with locally restricted de‐ and remyelination. Abstract : Microglia induce MHC II expression upon activation, but its functional implication to brain pathologies remains unclear. Here, we establish using targeted mutagenesis that microglial MHC II is in contrast to earlier notions dispensable for the onset of EAE and de‐ and remyelination reaction induced by cuprizone.